Harnessing PET Waste for High-Performance Composite Boards in Green Building Applications - Mat Nawi, Siti Nur Amani Alia; Burhanudin, Mohd Khairy; Md Noh, Mohammad Soffi; Kamaruddin, Khairol; Josef Hadipramana (International Journal of Sustainable Construction Engineering and Technology, 2026)
This study investigates the compressive and tensile properties of PET composite boards made from post-consumer plastic waste (PET), spent garnet, and sand for application in green building technology. Laboratory tests were conducted to evaluate the composites’ mechanical performance, particularly in optimising the binder-to-filler ratio and filler composition. The results indicate that increasing PET content significantly enhances compressive strength, with Mixes 12 and 13 achieving the highest compressive strength (12-16.5 MPa). Tensile strength ranged from 2.63 MPa to 8.58 MPa and was more influenced by filler composition. Regression models for both strengths revealed significant dependence on the binder-to-filler ratio and filler composition. ANOVA analysis confirmed the significance of these factors in enhancing mechanical performance. Diagnostic plots validated the regression models, indicating good data fit. Despite these promising results, the PET composites demonstrated relatively low tensile strength, indicating the need for further reinforcement, such as fibre inclusion. Additionally, the study did not address long-term durability under environmental stressors, highlighting a critical area for future research. Recommendations include exploring fibre reinforcement, evaluating long-term performance, and conducting lifecycle analysis to assess the environmental impact. This research contributes to developing sustainable construction materials by optimising the composition of PET composite boards, with potential application in non-structural building elements.